MONITORING AND TRACKING SYSTEM OF VEHICLES USING GIS, GPS AND GPRS TECHNOLOGY AT TIMOR LESTE - Muchlisin, Yazid Dul (SAINTIS Jurnal ilmu-ilmu eksakta, 2024)
Along with the development of the age and the economy in the Timor Leste an increasing number of vehicles present a significant potential to create disorder, violation of traffic signs, vehicle lane violations, and theft of vehicles, both vehicles are moving or parked, to the smooth, security and management targets that move like cars government, trucks, buses, airplanes and so on, needed a system for controlling and monitoring a moving object from other places through long distance communication lines, such as taxi fleet tracking, tracking for car rental services, tracking for trucks carrying food, tracking for rail, airplane tracking, etc, are objects and targets that need to be supervised and monitored in order to function properly. Vehicle tracking system using GPS and GPRS integration googlemaps provide information that is maximized with the technology of a GPS (Global Positioning System) receiver, which can indicate the position of the vehicle with the map and the ability of the appointment of direction and position coordinates (x, y, latitude, longitude) textually and visually at any location. A vehicle tracking system is built using equipment GIS (Geographic Information System) and dedicated to smartphones, which support the Global Positioning System (GPS), as well as portable computers, using General Packet Radio Service (GPRS) as a connection to the internet. The hardware used is a smartphone that supports GPS, and the supporting tools used are Google Maps, The results of this system in the form of a tracking system capable of monitoring the movement of vehicles in an ongoing position by utilizing GPS and GPRS as the senders of the wireless data and Internet connections.